Prevalence of Chlamydia trachomatis, Neisseria gonorrhoeae, Mycoplasma genitalium and Ureaplasma urealyticum infections using a novel isothermal simultaneous RNA amplification testing method in infertile males - Ling Qing; Qi-Xiang Song; Jian-Li Feng; Hai-Yan Li; Guiming Liu; Hai-Hong Jiang (BMC, 2017)
Abstract Background The purpose of this study was to evaluate the prevalence of Chlamydia trachomatis, Neisseria gonorrhoeae, Mycoplasma genitalium and Ureaplasma urealyticum infections in infertile men that consulted our outpatient departments using a novel simultaneous amplification testing (SAT) that is RNA-detection based. The possible impact of C. trachomatis, N. gonorrhoeae, M. genitalium and U. urealyticum infections on semen parameters was also noted in the present study. Methods A total of 2607 males that were diagnosed with infertility were included in this study. C. trachomatis, N. gonorrhoeae, M. genitalium and U. urealyticum infections were detected in the urine samples using SAT method. Related data, including semen parameters and age as well as C. trachomatis, N. gonorrhoeae, M. genitalium and U. urealyticum infections were collected and analyzed. Results A total of 51 and 1418 urine samples were found positive for M. genitalium RNA and U. urealyticum RNA, respectively, while the prevalence of C. trachomatis and N. gonorrhoeae was relatively lower. Men with positive M. genitalium RNA and U. urealyticum RNA had higher sperm DNA fragmentation index (DFI) while the comparisons of other semen parameters yielded nonsignificant results between the RNA positive and negative group. A multivariate linear regression analysis revealed that U. urealyticum and M. genitalium infections posed significant factors of DFI (adjusted R2 = 46.2%). Conclusions Our study suggested a relative high prevalence of U. urealyticum and M. genitalium infection based on this novel SAT detection method. U. urealyticum and M. genitalium infection could possibly impair male fertility potential through promoting sperm DNA damage.